Infections of reproductive organs in female rabbits - L. V. Koreyba; V. V. Hlebeniuk; V. M. Plys (Науковий вісник Львівського національного університету ветеринарної медицини та біотехнологій імені С.З. Ґжицького: Серія Ветеринарні науки)
Symptomatic infertility is a temporary or permanent disturbance in reproductive function wherein the animal cannot become pregnant due to diseases of genital organs or systemic diseases. Since female rabbits, due to their precociousness and fertility, are often used for reproduction, the leading causes of symptomatic infertility in them are the absence of estrous cycles or their deficiency and inflammation of tissues of the reproductive system. Infertility is observed in female rabbits developing such infectious diseases as pasteurellosis, spirochetosis, and myxomatosis. It is due to these diseases that obstetric and gynecological pathology (vulvitis, vulvovaginitis, metritis, pyometra, mastitis), long-term infertility, and death of animals are recorded most often. External genitalia (vulva) and mammary glands are the main routes of infection in female rabbits. The most common microorganisms causing inflammatory processes in reproductive organs are non-specific, such as Staphylococcus and Pasteurella, and specific microbes, such as toxoplasma. Spirochetes, Listeria, and Salmonella are much less common. It has been found that on farms of different forms of ownership in the Dnipropetrovsk region, the most common infectious diseases in rabbits are myxomatosis (20 %), viral hemorrhagic disease (13 %), eimeriosis (30 %), pasarulosis (10 %), and spirochetosis (10 %). Inflammation of genital tissues, especially inflammatory processes in the uterus, is the most common disease in female rabbits. The general frequency of uterine diseases increases with age, reaching more than 50% in aged female rabbits. Endometritis was the most frequent inflammatory process diagnosed in 10 % of cases and was potentially purulent, catarrhal, lymphoplasmacytic, or enterohemorrhagic. Metritis was observed in 5 % of cases and pyometra in 3 %. Autopsy of forcibly slaughtered or dead animals revealed such uterine diseases as hydrometer and mucometer. Hydrometers and mucometers comprised 8 % of uterine diseases, and the average age of sick female rabbits was 3 years. The etiology remains unclear but is potentially related to endometrial hyperplasia or endometritis. However, in some cases, no underlying uterine disease was found. During acute infection of the organs of the reproductive system of female rabbits, a serous mucocatarrhal or mucopurulent exudate is released from the genital slit. Chronic inflammatory processes of the genital organs often occur without signs of disease or are manifested by decreased fertility or abortion.